Percutaneous Patent Foramen Ovale Closure in Patients with Cryptogenic Stroke or Transient Ischemic Attack: A Retrospective Study. (30th January 2022) - Liu, Yuan; He, Yongming; Hui, Pinjing; Li, Tan; Zhu, Juehua; Zhao, Caiming; Zhang, Quanquan; Fang, Qi
Abstract : Background . Patent foramen ovale (PFO) is associated with cryptogenic stroke (CS). Transcatheter closure of PFO is superior to pharmacotherapy for patients with CS or transient ischemic attack (TIA). More evidence is needed to evaluate the efficacy and safety of PFO closure in Chinese patients. Methods . This study enrolled ten CS patients and two TIA patients (mean age of 40.8 ± 9.7 y), including seven males (58%) and five females (42%) who underwent PFO closure in our center from January 2017 to July 2019. Baseline data, imaging data, and RoPE (Risk of Paradoxical Embolism) score were collected retrospectively. The preprocedural assessment and percutaneous transcatheter PFO closure were described in detail. The perioperative complications and follow-ups were recorded from all patients. Results . Among ten patients with CS, eight patients had a RoPE score of >6 and two patients had a RoPE score of 6. MRI confirmed multiple infarcts in seven cases, and infarct involving the cortex in nine cases. Abnormal ECG was found in three patients and abnormal Echo in four patients. Right-to-left shunt (RLS) was detected in all the patients by cTCD or cTTE. To be specific, RLS was observed in nine of the ten TEE-detected patients. No case had PFO complicated with atrial septal aneurysm (ASA). The success rate of PFO closure was 91.6%. No serious perioperative complications were observed. During a mean time of 26.5 ± 8 months (15-41 months) of follow-up, no recurrent cerebral infarction, TIA, or thromboembolism were detected in postoperative patients. Conclusions . PFO closure is safe and effective in the treatment of Chinese patients with CS or TIA.